2022
DOI: 10.3389/fcimb.2022.835654
|View full text |Cite
|
Sign up to set email alerts
|

EhVps23, an ESCRT-I Member, Is a Key Factor in Secretion, Motility, Phagocytosis and Tissue Invasion by Entamoeba histolytica

Abstract: The EhVps23 protein, an orthologue of the yeast Vps23 and the mammalian TSG101 proteins, is the single member of the ESCRT-I complex of Entamoeba histolytica identified and characterized until now. EhVps23 actively participates in vesicular trafficking and phagocytosis, which influence several cellular events. In this paper, we investigated the role of EhVps23 in virulence-related functions, including the invasive capacity of trophozoites, using transfected trophozoites. Trophozoites overexpressing the EhVps23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 41 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…As EhADH, EhVps23 could play a role at various points of the endocytic pathway. Another experimental data on the relevance of EhVps23 in phagocytosis is the fact that trophozoites overexpressing EhVps23 migrate five-fold faster than control parasites, in concordance with the low rate of migration exhibited by Ehvps23-knocked down trophozoites (Galindo et al, 2022); this, points out to the participation of the ESCRT machinery also in motility, a fundamental event for phagocytosis. In regard to EhVps37, Loṕez-Reyes et al ( 2010) found an EhVps37D protein lacking the alpha helixes required for ESCRT-I binding (Kostelansky et al, 2007;Galindo et al, 2021).…”
Section: Multivesicular Bodies Biogenesissupporting
confidence: 58%
See 4 more Smart Citations
“…As EhADH, EhVps23 could play a role at various points of the endocytic pathway. Another experimental data on the relevance of EhVps23 in phagocytosis is the fact that trophozoites overexpressing EhVps23 migrate five-fold faster than control parasites, in concordance with the low rate of migration exhibited by Ehvps23-knocked down trophozoites (Galindo et al, 2022); this, points out to the participation of the ESCRT machinery also in motility, a fundamental event for phagocytosis. In regard to EhVps37, Loṕez-Reyes et al ( 2010) found an EhVps37D protein lacking the alpha helixes required for ESCRT-I binding (Kostelansky et al, 2007;Galindo et al, 2021).…”
Section: Multivesicular Bodies Biogenesissupporting
confidence: 58%
“…and mass spectrometry analysis, our group detected EhVps26 and EhVps35 as interacting partners of EhVps23 (Galindo et al, 2022).…”
Section: Retromermentioning
confidence: 89%
See 3 more Smart Citations